Mechanized visions: Gendered pathway in innovations - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Waswa, Boaz Shaban (2024)
Women are engaging, questioning, and learning how to use technologies designed for them. They are also making sure it is available for other women.